Preoperative Anterior and Posterior Tilt of Garden I-II Femoral Neck Fractures Predict Treatment Failure and Need for Reoperation in Patients Over 60 Years - Pontus Sjöholm, MD (Wolters Kluwer, 2021)
Background:. The purpose of the present study was to estimate the effect of preoperative fracture tilt and to scrutinize the effect of anterior tilt on the risk of treatment failure in patients with Garden Type-I and II femoral neck fractures that are treated with internal fixation. Methods:. A retrospective multicenter study was performed on a consecutive series of patients ≥60 years of age who had undergone primary internal fixation for the treatment of Garden Type-I and II femoral neck fractures. The study included 1,505 patients with a minimum follow-up of 2 years. Radiographic assessments encompassed preoperative and postoperative tilt, implant inclination, and treatment failure. Data on reoperation and mortality were collected. The risk of treatment failure was assessed with use of Cox proportional hazard regression analysis. Results:. The study comprised 1,505 patients (71% female) with a median age of 81 years (range, 60 to 108 years). Overall, 234 patients (16%) were classified as having a treatment failure and 251 patients (17%) underwent reoperation. A preoperative anterior tilt of >10° and a posterior tilt of >20° were predictors of treatment failure and reoperation, respectively. Treatment failure occurred in 74 (25%) of 301 patients with a posterior tilt of >20° and in 17 (43%) of 40 patients with an anterior tilt of >10°. Conclusions:. This multicenter cohort study identified a subgroup of patients with Garden Type-I and II femoral neck fractures with an anterior tilt of >10° as having high treatment failure rates and major reoperation rates comparable with those associated with displaced femoral neck fractures. A preoperative posterior tilt of >20° increases the risk of treatment failure, and the potential benefit of arthroplasty in this subgroup of patients remains to be further investigated. Level of Evidence:. Prognostic Level III. See Instructions to Authors for a complete description of levels of evidence.